2010
DOI: 10.3109/07420521003794069
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Effect in Humans of Suppressed Endogenous Melatonin by Pre-Sleep Bright-Light Exposure in a Cold Environment

Abstract: This study investigated the physiological function of suppressed melatonin through thermoregulation in a cold environment. Interactions between thermoregulation directly affected by exposure to a cold environment and indirectly affected by endogenous melatonin suppression by bright-light exposure were examined. Ten male subjects were exposed to two different illumination intensities (30 and 5000 lux) for 4.5 h, and two different ambient temperatures (15 and 27 degrees C) for 2 h before sleep under dark and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…This inverse relationship could be explained by the alerting properties of light through sympathetic activation inducing blood-vessel constriction and, in turn, reduction in skin temperature (Buijs et al, 2003). Other authors have demonstrated the short-term effect of bright-light exposure on reducing melatonin and sleepiness and on increasing alertness, heart rate, and core temperature (Cajochen et al, 2005;Ishibashi et al, 2010;Phipps-Nelson et al, 2009). Laboratory studies have suggested that short, intermittent periods of exposure to bright light, such as those characteristic of our modern lifestyle, may have a much greater impact on circadian entrainment than has previously been recognized (Hebert et al, 1998;Okudaira et al, 1983;Savides et al, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…This inverse relationship could be explained by the alerting properties of light through sympathetic activation inducing blood-vessel constriction and, in turn, reduction in skin temperature (Buijs et al, 2003). Other authors have demonstrated the short-term effect of bright-light exposure on reducing melatonin and sleepiness and on increasing alertness, heart rate, and core temperature (Cajochen et al, 2005;Ishibashi et al, 2010;Phipps-Nelson et al, 2009). Laboratory studies have suggested that short, intermittent periods of exposure to bright light, such as those characteristic of our modern lifestyle, may have a much greater impact on circadian entrainment than has previously been recognized (Hebert et al, 1998;Okudaira et al, 1983;Savides et al, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…Forty‐five papers have been finally collected to review the most recent studies on combined effects of environmental factors upon human performance and comfort. Details are provided in the Appendix S1 (SI.2) and in particular in Table SI.1.…”
Section: Methodsmentioning
confidence: 99%
“…Fewer studies have been carried out on the direct effect of light intensity on thermal sensation and thermal comfort. Two studies found a cooler thermal sensation under low light intensity as compared to bright light, while the third experiment reported no significant effect of light intensity on thermal comfort and thermal sensation . Additionally, changes in thermal sensation caused by the intensity of light may be related to changes in core body temperature .…”
Section: Introductionmentioning
confidence: 93%